The Blockchain Integration in Cloud Accounting for Financial Statement Recognition - Siregar, Yentina; Hisyam, Magneta (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The rise of cryptocurrency and blockchain technology has introduced a paradigm shift in various sectors, including finance and accounting. This paper explores the integration of blockchain technology in recognizing financial statements in cloud accounting systems. This study employs a qualitative literature review method to explore the intersection of blockchain technology, cryptocurrency, and financial statement recognition within cloud accounting systems. Relevant peer-reviewed articles, books, and industry reports published between 2010 and 2025 were systematically collected, screened using defined inclusion and exclusion criteria, and thematically analyzed to synthesize key concepts, identify patterns, and highlight research gaps. The result shows that blockchain's decentralized, secure, and transparent nature makes it an ideal tool for improving the accuracy, security, and efficiency of financial reporting. By leveraging blockchain to record transactions and manage financial data, businesses can ensure that their financial statements are tamper-proof and provide real-time, auditable records. The cloud accounting environment, combined with blockchain, promises enhanced collaboration, real-time updates, and greater transparency between stakeholders. This paper examines the potential benefits and challenges of integrating blockchain into cloud-based financial systems and how it could reshape the future of accounting practices, providing a more secure, efficient, and transparent framework for financial reporting.